Towards a Modern Leadership: Sustainable Development-Oriented Management - Mihaela Simionescu; Cristinel Vasiliu; Corina-Georgiana Serban (Patrintas); Andreea-Nicoleta Bichel; Oana Simona Hudea (Amfiteatru Economic, 2023)
The new context generated by the series of crises having occurred at the global level (the COVID-19 pandemic, the Ukraine war, the price increases) brings to our attention the sustainable development-oriented management of organisations. The purpose of this paper is to outline the importance of adapting management styles to the requirements of the current economic context and to the sustainability-related challenges. The efficient communication, the cohesion, and the development of personal relationships are essential for creating a productive and pleasant work environment. The main research methods used in order to achieve such a goal are: principal component analysis, matching propensity score, binary logistic regression, multilevel binary logistic regression, and structural equation models. The results reveal that the long-term orientation of leaders towards sustainability is influenced by factors such as gender, age, position within the organisation, type of organisation where they carry out their activity, but also by a series of personal qualities and features. This article is a novelty for Romania, as it fills a gap in the related scientific literature on the relationship between the characteristics of a leader and the role of the same in the implementation of sustainability in the organisational environment. The output reflects the appreciations that the employees operating in the organisational environment manifest with respect to the features of sustainability-oriented leaders, as well as to their long-term role in promoting sustainability. Furthermore, the implications regarding the promotion of good practices in sustainability, among both managers and employees, are identified, taking into consideration the dynamic rhythm of the business environment and the ever-complex sustainability-related requirements.
Keywords: Q01; M15; M54; 330; sustainability; sustainable development; leader; leadership; strategy.